Understanding client satisfaction with a health insurance scheme in Nigeria: factors and enrollees experiences - Mohammed, Shafiu; Sambo, Mohammad N.; Dong, Hengjin (Health research policy and systems, 2011)
Health insurance schemes have been widely introduced during this last decade in many African countries, which have strived for improvements in health service provision and the promotion of health care utilization. Client satisfaction with health service provision during the implementation of health insurance schemes has often been neglected since numerous activities take place concurrently. The satisfaction of enrollees and its influencing factors have been providing evidence which have assisted in policy and decision making. Our objective is to determine the enrollee's satisfaction with health service provision under a health insurance scheme and the factors which influence the satisfaction.